Synthesis and characterization of undoped and doped ZnO nanoparticles prepared by sol-gel process - Ali, Abdub Guyo (University of the Free State, 2009)
Nanotechnology is an emerging field of engineering that has intrigued a tremendous potential to change today's lives. Nanoparticles represent the transition region between individual atom/molecule and bulk materials have been attracting considerable research input, owing to some unique physical and chemical properties they exhibit. They are already being used in many applications. This is due to their potential useful size and shape dependant. They are provided with a number of quantum size effects that determine specific electro-physical performance. This is one of the reasons why the preparation and study of nanomaterials are important area of research. This work focuses on the synthesis and characterization of semiconducting metal oxides, the most widely used materials in powder and films forms. The aim is to compare the optical performances of zinc-oxides nanostructures obtained by means of sol-gel (SG) method. The microstructure quality (concentration and nature of defects) of materials which is a fundamental parameter to evaluate if the material is suitable for any applications are usually correlated with optical properties (intensity and spectral emission range) of materials. The idea of this work was to carry a basic characterization of the structural (by X-ray diffraction technique and scanning electron microscopy) and optical (photoluminescence measurements) properties of ZnO, ZnO in SiO2 matrix and manganese doped ZnO nanoparticles samples prepared by sol-gel process. Initially, several samples of ZnO nanoparticles were successfully synthesised by varying the pH of the precursors. Secondly, manganese doped ZnO samples were synthesised by varying the concentration of manganese. The analysis of ZnO nanoparticles prepared under varying pH has displayed a dependence of structural quality, morphology as well as optical properties on the pH of the precursors. SEM images of manganese doped ZnO samples reveal nanorods of micrometer-size. XRD patterns confirm polycrystalline wurtzite structure of ZnO and particle sizes of about 7nm. High optical transmittance greater than 80% was achieved in the visible spectral wavelengths with UV-Vis optical absorption and transmission measurements. Photoluminescence spectra of the pure ZnO are composed of two main emission bands peaked at 388nm and 569nm. Both the blue (388nm) and the green (560nm) emissions in ZnO nanostructures were quenched, although to different extent, when doped with Mn2+. Mn-doped ZnO nanorods have several applications as the most suited materials for sensors, spintronics, better insulation materials etc.
Dissertation (M.Sc. (Physics))--University of the Free State (Qwaqwa Campus), 2009
Keywords: Nanotechnology; Electro-physical performance; X-ray diffraction technique; ZnO in SiO2 matrix and manganese; Optical properties on the pH